2016
DOI: 10.3332/ecancer.2016.696
|View full text |Cite
|
Sign up to set email alerts
|

Solitary thyroid metastasis from colon cancer: a rare case report

Abstract: Malignant metastases to the thyroid are rare and are even rarer from a colorectal primary. As these metastases are often asymptomatic, they are usually discovered incidentally on imaging performed as follow-up for the primary tumour. In this report, we present a case of metastatic sigmoid adenocarcinoma to the thyroid diagnosed and treated at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Colorectal carcinomas metastasizing to the thyroid gland is extremely rare. Metastases to the thyroid gland often present asymptomatically and are only incidentally discovered on follow-up scans for a patient’s primary tumor [ 5 ]. According to Coelho et al, metastases to the thyroid, if symptomatic, will commonly present with swelling and cervical mass, or have goiter-related symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal carcinomas metastasizing to the thyroid gland is extremely rare. Metastases to the thyroid gland often present asymptomatically and are only incidentally discovered on follow-up scans for a patient’s primary tumor [ 5 ]. According to Coelho et al, metastases to the thyroid, if symptomatic, will commonly present with swelling and cervical mass, or have goiter-related symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the primary tumor is usually the lung, kidney, or breast depending on the series [7][8][9] . Metastases of colorectal cancer on the thyroid are extremely rare and are usually diagnosed after several years of follow-up 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Metastases in the thyroid gland are unusual. They appear in 1.4-3% of patients whose initial suspicion was thyroid carcinoma 4 . However, studies of autopsies of subjects with disseminated neoplasms have found between 2 and 24% of metastases on this gland 5,6 .…”
Section: Introductionmentioning
confidence: 99%